Comparison of oncologic and functional outcomes between radical nephroureterectomy and segmental ureterectomy for upper urinary tract urothelial carcinoma - Kim, Tae Heon (Sci Rep, 2021)
This study aims to compare oncologic and functional outcomes after radical nephroureterectomy (RNU) and segmental ureterectomy (SU) in patients with upper urinary tract urothelial carcinoma (UTUC). We retrospectively collected data on patients who underwent either RNU or SU of UTUC. Propensity score matching was performed among 394 cases to yield a final cohort of 40 RNU and 40 SU cases. Kaplan–Meier analysis and the log-rank test were used to compare overall survival (OS), cancer-specific survival (CSS), progression-free survival (PFS), and intravesical recurrence-free survival (IVRFS) between the groups. We also compared the change in postoperative estimated glomerular filtration rate (eGFR). There was no significant difference in terms of CSS, PFS, and IVRFS between the RNU and SU groups, but the RNU group had a better OS than the SU group (p = 0.032). Postoperative eGFR was better preserved in the SU group than in the RNU group (p < 0.001). SU provides comparable CSS, PFS, and IVRFS for patients with UTUC compared to RNU, even in patients with advanced-stage and/or high-grade cancer. Further, SU achieves better preservation of renal function.